2020
DOI: 10.1136/bmjopen-2020-040580
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial for high-dose intravenous zinc as adjunctive therapy in SARS-CoV-2 (COVID-19) positive critically ill patients: trial protocol

Abstract: IntroductionSARS-CoV-2 (COVID-19) has caused an international pandemic of respiratory illness, resulting in significant healthcare and economic turmoil. To date, no robust vaccine or treatment has been identified. Elemental zinc has previously been demonstrated to have beneficial effects on coronaviruses and other viral respiratory infections due to its effect on RNA polymerase. Additionally, zinc has well-demonstrated protective effects against hypoxic injury—a clear mechanism of end-organ injury in respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…These researchers have reported that having low levels of serum zinc (< 50 μg/dL at the admission) is a risk factor that will determine the COVID-19 outcome, including a higher mortality. In turn, Perera et al (2020) conducted a double-blind randomized controlled trial of daily high-dose intravenous zinc (0.5 mg/kg) versus placebo. There were 160 hospitalized participants, including 100 critically ill patients with confirmed COVID-19.…”
Section: Essential Trace Elements and Covid-19mentioning
confidence: 99%
“…These researchers have reported that having low levels of serum zinc (< 50 μg/dL at the admission) is a risk factor that will determine the COVID-19 outcome, including a higher mortality. In turn, Perera et al (2020) conducted a double-blind randomized controlled trial of daily high-dose intravenous zinc (0.5 mg/kg) versus placebo. There were 160 hospitalized participants, including 100 critically ill patients with confirmed COVID-19.…”
Section: Essential Trace Elements and Covid-19mentioning
confidence: 99%
“…Rapid improvements in symptoms, including fever, dyspnea and hypoxia, were reported in a consecutive case series receiving high-dose zinc rescue with different preparations. (5) A randomized controlled trial for high-dose intravenous zinc was initiated as adjunctive therapy in SARS-CoV-2-positive critically ill patients (30). H322M was therefore treated with 24-hour serial doses of 18.75, 37.5, 75, 150 and 300 µM ZnSO4 (Zn) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed clinical trial protocol has been published previously 19 . Briefly, we randomized consenting COVID‐19 confirmed hospitalized adults with oxygen saturation (SpO 2 ) of 94% or less while on ambient air to either daily HDIVZn or saline placebo.…”
Section: Methodsmentioning
confidence: 99%